Nutritive evaluation of some tree leaves from Bangladesh for feeding ruminant animals - KHAN, M J; DROCHNER, W; STEINGASS, H; ISLAM, K M S (The Indian Journal of Animal Sciences, 2011)
Potential nutritive value of 10 species of tree leaves (Streblus asper, Ficus infectoria, MOrLlS alba, Mang~fera indica, Erythrina indica, Albizia spp, Artocalpus integrifolia, Leucaena leucocephala, Zizyphus nzauritiarza and Sesbania sesban) of Bangladesh was studied. Chemical conlposition, fractions, mineral concentration, mnino acid contents, in vitro organic matter digestibility and energy values showed a wide variation among the species. Crude protein (CP) ranged froll1 8.5 to 23.9%, and M. alba showed the highest and M. indica the lowest. CP, EE, NFE, ash and CF were 26.2,2.2,48.5,9.1 and 13.70/0 respectively. The CF fractions, viz. NDF, ADF, ADL, cellulose and hemicellulose were 55.1, 43.3,15.9,25.7 and 11.8% respectively. Mineral concentration varied among species but all leaves were rich in Ca and p~ and moderate in K, Fe and Co. M. indica was inferior in CP but there was very little variation in individual and total amino acid contents. Organic matter digestibility ranged 41.2 to 76.90/0 with 53.4% digestibility. All the leaves \vere quite rich in gross and metabolizable energy (ME) but poor in net energy for lactation. In conclusion the tree leaves, especially M. alba, S. sesban, L. leucocephala and S. asper have the great potential to be used as feed for livestock considering nutritive points of view.Â